Akibat Hukum dan Keabsahan Dari Akta Jual – Beli yang Dibuat Diatas Perjanjian Jual – Beli yang dilakukan Seolah-Olah (Studi Kasus Putusan di Pengadilan Negeri Kudus Nomor: 13/Pdt.G/2016/PN.Kds) - Puspa Hartanto, Adinda; Gunadi, Ariawan (LPPM Universitas Ekasakti Padang, 2024)
Humans are social beings who have interests that they want to achieve. When an interest cannot be fulfilled, he will try to find someone who can fulfill his interests which will meet the interests of the other party which brings a good reciprocal effect, so an agreement is made. In order for there to be legal certainty in the agreement, the making of the agreement is carried out before a Notary. Notary is one of the officials who has the authority to make documents in the form of authentic deeds which are written evidence that has strong and absolute evidentiary power where if the parties do not recognize the authentic deed, both parties must provide evidence that denies the deed in accordance with what is written in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions. Even though there is a governing law, we still often find Notaries who commit several violations that cause losses to clients as happened in one of the Holy District Court Decisions Number: 13 / Pdt.G / 2016 / PN.Kds where Notaries make Sale and Purchase Agreements as if and without an agreement between the two parties